The Epanechnikov-Rayleigh Distribution: Statistical Properties and Real-World Applications (Statistics, Optimization & Information Computing, 2025)
This article looks at the main statistical features of the Epanechnikov-Rayleigh Distribution, like moments and quintiles, and figures out the probability density function (PDF) and cumulative distribution function (CDF). Maximum likelihood estimation (MLE) is used for parameter estimation, and comprehensive simulation studies are used to assess the suggested distribution's performance. The superior goodness-of-fit of the Epanechnikov-Rayleigh distribution over the classical Rayleigh distribution and other competing models is demonstrated by real-world applications in reliability analysis and environmental modeling, as evaluated by the Bayesian Information Criterion (BIC) and Akaike Information Criterion (AIC).